Recent advances in autoimmune encephalitis - João Henrique Fregadolli Ferreira; Caio César Diniz Disserol; Bruna de Freitas Dias; Alexandre Coelho Marques; Marina Driemeier Cardoso; Pedro Victor de Castro Silva; Fabio Fieni Toso; Lívia Almeida Dutra (Arquivos de Neuro-Psiquiatria)
Since the description of autoimmune encephalitis (AE) associated with N-methyl-D-aspartate receptor antibodies (anti-NMDARE) in 2007, more than 12 other clinical syndromes and antibodies have been reported. In this article, we review recent advances in pathophysiology, genetics, diagnosis pitfalls, and clinical phenotypes of AE associated with cell surface antibodies and anti-GAD associated neurological syndromes. Genetic studies reported human leukocyte antigen (HLA) associations for anti-LGI1, anti-Caspr2, anti-IgLON5, and anti-GAD. Follow-up studies characterized cognitive dysfunction, psychiatric symptoms, sleep disorders, and adaptative behavior dysfunction, mainly for anti-NMDARE. Late-onset anti-NMDARE and anti- GABA-B receptor (GABA-BR) encephalitis patients were described to have worse prognoses and different tumor associations. Additionally, the clinical spectrum of anti-LGI1, anti-AMPAR, anti-CASPR2, and anti-IgLON5 was expanded, comprising new differential diagnoses. The diagnostic criteria for AE were adapted to the pediatric population, and a diagnostic algorithm was proposed, considering potential mimics and misdiagnosis. We also review the limitations of commercial assays for AE and treatment recommendations, as well as clinical scales for short and long-term assessment of AE patients, along with cognitive evaluation.